The evolution of coral reef monitoring in eastern Arabia: trends, gaps, and opportunities for the ROPME Sea Area - Hannah Gower; Hannah Gower; Jeneen Hadj-Hammou; John A. Burt (Frontiers in Marine Science)
Coral reefs are the most biodiverse ecosystem in eastern Arabia, which includes the Arabian Gulf, Gulf of Oman, and Western Arabian Gulf, an area collectively known as the ROPME Sea Area under UN convention. However, regional reefs are under growing threat from global climate change to local population-related pressures. This systematic review provides the first region-wide assessment of coral reef monitoring efforts, identifying 105 publications spanning almost four decades. Findings highlight a variety of research motivators, a diverse and evolving range of methods, and the inclusion of both citizen science and governmental projects alongside conventional scientific research. However, large disparities in monitoring efforts are evident between the countries as well as a concerning lack of international collaboration despite the transboundary nature of many regional coral reef stressors. The prevalence of short-term ‘snapshot’ studies and one-off authors also indicate the absence of a strong, continuous local research presence, undermining long-term conservation efforts. Most concerning is the recent decline in the volume of monitoring-related studies, both within scientific institutions and across multi-party projects, with research instead diverted to more novel areas of coral reef research. Given the ongoing regional reef decline, it is essential that monitoring efforts continue to grow, incorporating large-scale, long-term studies in order to accurately assess reef status and trends and assist in conservation.